1991
DOI: 10.1007/bf01783491
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in drinking water and mortality in the Southern Great Plain, Hungary

Abstract: Arsenic distribution has been found in drinking waters. A connection between arsenic and other constituents of water was determined. Close positive correlation was found between arsenic and humic substances over most of the study area. In two smaller areas, there was no correlation between arsenic and humic substances. In these waters, the arsenic distribution is not controlled by organic matter, but by other factors which need further investigations.Examination of mortality in the populations consuming water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Release of soluble As species into groundwater is a serious problem in many areas of the world (Varsanyi et al 1991;Lepkowski 1998;Welch et al 2000;Tian et al 2001;Bhattacharya et al 2002;Nickson et al 2005;Farooqi et al 2006Farooqi et al , 2007Guo et al 2011;Brahman et al 2013). A number of large aquifers in the various parts of the world have been reported with As >50 µg/L.…”
Section: World-wide Occurrences Of Arsenic and Fluoride Contaminated mentioning
confidence: 96%
“…Release of soluble As species into groundwater is a serious problem in many areas of the world (Varsanyi et al 1991;Lepkowski 1998;Welch et al 2000;Tian et al 2001;Bhattacharya et al 2002;Nickson et al 2005;Farooqi et al 2006Farooqi et al , 2007Guo et al 2011;Brahman et al 2013). A number of large aquifers in the various parts of the world have been reported with As >50 µg/L.…”
Section: World-wide Occurrences Of Arsenic and Fluoride Contaminated mentioning
confidence: 96%
“…From the point of view of groundwater contamination, As and F -have received the most attention due to their toxicity (e.g., Smedley et al, 2002). The release of soluble As species into groundwater is a serious problem in many areas of the world (e.g., Varsanyi et al, 1991;Lepkowski, 1998;Welch et al, 2000;Tian et al, 2001;Bhattacharya et al, 2004;Nickson et al, 2005). The World Health Organiza-fluorosis, if it is higher than 1.5 mg/L (CDCP, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…15,20,24 The World Health Organization (WHO) recommends an upper limit of 10 ng/ml for arsenic in drinking water. 25 The inorganic species arsenate and arsenite are the predominant form of arsenic in terrestrial plants, whereas organic species like DMA and MMA have only been found in relatively low concentrations.…”
Section: Introductionmentioning
confidence: 99%